2012
DOI: 10.1111/j.1365-2036.2012.05109.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of PNPLA3 polymorphism in chronic hepatitis C patients receiving peginterferon plus ribavirin

Abstract: SUMMARY BackgroundHomozygosity for the PNPLA3 p.I148M polymorphism influences steatosis and fibrogenesis in chronic hepatitis C (CHC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 38 publications
1
41
1
Order By: Relevance
“…The stronger effect of PNPLA3 in non-obese patients fits with a recent study showing that the amount of liver fat is similar in obese NAFLD compared to PNPLA3 rs738409 G-associated NAFLD. Our data confirmed the link reported in CHC between the severity of steatosis and the PNPLA3 rs738409 G variant, [8][9][10][11][12][13][14][15] but we were unable to confirm a direct association with the severity of fibrosis. Differences in clinical, metabolic and histological characteristics of studied populations, as well as in the analysis of data could explain this difference.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The stronger effect of PNPLA3 in non-obese patients fits with a recent study showing that the amount of liver fat is similar in obese NAFLD compared to PNPLA3 rs738409 G-associated NAFLD. Our data confirmed the link reported in CHC between the severity of steatosis and the PNPLA3 rs738409 G variant, [8][9][10][11][12][13][14][15] but we were unable to confirm a direct association with the severity of fibrosis. Differences in clinical, metabolic and histological characteristics of studied populations, as well as in the analysis of data could explain this difference.…”
Section: Discussionsupporting
confidence: 70%
“…[5][6][7] Some studies on cohorts of mostly genotype 1 (G1) chronic hepatitis C (CHC) patients have reported an association between the PNPLA3 rs738409 G variant and the severity of both steatosis and fibrosis, the risk of fibrosis progression and HCC occurrence, and the response to pegylated interferon plus ribavirin therapy. [8][9][10][11][12][13][14][15] Bedossa et al, in liver biopsies from CHC patients, recently characterised the presence of histological features of steatohepatitis, showing that the occurrence of NASH in this setting not only was related to a poor atrisk metabolic profile but was also a risk factor for the severity of liver damage. 16 This study however did not investigate the impact of genetic background on the presence of steatohepatitis in the context of CHC.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests metabolic steatosis rather than genetic steatosis to be the reason for treatment failure in this cohort of patients. The lack of association between PNPLA3 genotype and SVR has been recently confirmed by a collaborative study conducted in Italy and Austria where 602 naïve patients of any HCV genotype were treated with PegIFNalfa plus Ribavirin [21]. Overall, in that study SVR rates were 51 % in rs738409 GG and 59 % in CG/CC patients.…”
mentioning
confidence: 64%
“…The prevalence of PNPLA3 148M homozygotes in the Italian population has been reported to be approximately 10% (8-14%) [75,78,81]. In contrast, the homozygote frequency in Germany appears to be lower (5.5%) [82].…”
Section: Patatin-like Phospholipase Domaincontaining 3 (Pnpla3) and Impmentioning
confidence: 78%
“…Furthermore, this association has been corroborated in the setting of alcoholic liver disease and hepatocellular carcinoma [73,74]. In patients with HCV infection, homozygotes for the PNPLA3 148M similarly has been reported to be associated with more steatosis, fibrosis, cirrhosis and hepatocellular carcinoma predominantly in Mediterranean populations [75][76][77][78].…”
Section: Patatin-like Phospholipase Domaincontaining 3 (Pnpla3) and Impmentioning
confidence: 83%